2016
DOI: 10.1177/1045389x16672731
|View full text |Cite
|
Sign up to set email alerts
|

Principle, modeling, and control of a magnetorheological elastomer dynamic vibration absorber for powertrain mount systems of automobiles

Abstract: This article proposes and validates the principle of a new magnetorheological elastomer (MRE) dynamic vibration absorber (DVA) for powertrain mount systems of automobiles. The MRE DVA consists of a vibration absorption unit and a passive vibration isolation unit. The vibration absorption unit composed of a magnetic conductor, a shearing sleeve, a bobbin core, an electromagnetic coil, and a circular cylindrical MRE is utilized to absorb the vibration energy, and the passive vibration isolation unit is used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…After that, the research on vibration MRE-based absorbers developed quickly (e.g., Refs. [13,[108][109][110][111][112]). Figure 15 shows the sketch of a designed MRE-based vibration absorber composed of a semi-active vibration absorption unit and a passive vibration isolation unit.…”
Section: Vibration Absorbersmentioning
confidence: 99%
“…After that, the research on vibration MRE-based absorbers developed quickly (e.g., Refs. [13,[108][109][110][111][112]). Figure 15 shows the sketch of a designed MRE-based vibration absorber composed of a semi-active vibration absorption unit and a passive vibration isolation unit.…”
Section: Vibration Absorbersmentioning
confidence: 99%
“…Their results showed that the ATVA using MR elastomer materials can effectively work in a frequency ranging from 7 Hz–70 Hz. Xin et al [ 133 ] proposed and validated the principle of a new ATVA for powertrain mount systems of automobiles. Recently, Sun et al [ 134 ] proposed the eccentric mass on the top of the multilayered MR elastomer structured VA for vibration reduction, as seen in Figure 11 a.…”
Section: Applications Of Mr Elastomersmentioning
confidence: 99%
“…Active mounts can achieve better vibration isolation and relative displacement control performance in a broader frequency bandwidth via active force [3][4][5]. In the research of active mounting systems, the actuators and control methods that directly affect system performance have received extensive attention [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%